2015
DOI: 10.1248/bpb.b15-00009
|View full text |Cite
|
Sign up to set email alerts
|

Piceatannol Lowers the Blood Glucose Level in Diabetic Mice

Abstract: We previously found that passion fruit (Passiflora edulis) seeds contained a high amount of piceatannol (3,5,3′,4′-trans-tetrahydroxystilbene), a natural analog of resveratrol (3,5,4′-trans-trihydroxystilbene). Resveratrol has been proposed as a potential anti-metabolic disorder compound, by its activation of sirtuin and AMP-activated protein kinase. Many reports show that resveratrol ameliorates diet-induced obesity and insulin resistance. However, it is not known whether piceatannol also affects diet-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 25 publications
2
44
1
Order By: Relevance
“…However, when the positive control Metformin (500 mg.kg -1 ), an oral hypoglycemic standard of the biguanide class, was used a decrease in blood glucose at all evaluation periods (30 to 120 min) was observed compared to the hyperglycemic group (table 3). Metformin mechanism of action involves the inhibition of glucose uptake by the gastrointestinal tract, reduction of hepatic glucose production and increase of the sensitivity of peripheral tissues to insulin, enabling alterations of the glucose metabolism by inhibiting postprandial glucose elevation in approximately 25 to 30% [50], as verified in the present study. ) compared to the hyperglycemic control.…”
Section: Effect Of the Ethyl Acetate Fraction Of P Cincinnata On Thesupporting
confidence: 78%
“…However, when the positive control Metformin (500 mg.kg -1 ), an oral hypoglycemic standard of the biguanide class, was used a decrease in blood glucose at all evaluation periods (30 to 120 min) was observed compared to the hyperglycemic group (table 3). Metformin mechanism of action involves the inhibition of glucose uptake by the gastrointestinal tract, reduction of hepatic glucose production and increase of the sensitivity of peripheral tissues to insulin, enabling alterations of the glucose metabolism by inhibiting postprandial glucose elevation in approximately 25 to 30% [50], as verified in the present study. ) compared to the hyperglycemic control.…”
Section: Effect Of the Ethyl Acetate Fraction Of P Cincinnata On Thesupporting
confidence: 78%
“…Both RES and PIC are known to activate sirtuin 1 (SIRT1), a NAD + -dependent deacetylase linked to the regulation of life span and caloric restriction (Kahyo et al 2008;Baur 2010). We have previously reported that PIC displays a variety of biological activities, such as skin protection (Matsui et al 2010;Maruki-Uchida et al 2013), vasodilatation (Sano et al 2011;Kinoshita et al 2013), and lowering of blood glucose levels (Uchida-Maruki et al 2015). Furthermore, we used an in vivo (rat) model to demonstrate that the oral absorption of PIC is superior to that of RES, and that methylated metabolites, including isorhapontigenin (IRP), were detected in the plasma of animals dosed with PIC, but not those dosed with RES (Setoguchi et al 2014).…”
Section: Piceatannol Exhibits Anti-inflammatory Effects On Macrophagementioning
confidence: 99%
“…), and lowering of blood glucose levels (Uchida‐Maruki et al. ). Furthermore, we used an in vivo (rat) model to demonstrate that the oral absorption of PIC is superior to that of RES, and that methylated metabolites, including isorhapontigenin (IRP), were detected in the plasma of animals dosed with PIC, but not those dosed with RES (Setoguchi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, food safety is enhanced and the byproducts have a noble destination, also reducing the amount of wastes disposed of in the environment (Ferrari, Colussi, & Ayub, ; Haminiuk, Maciel, Plata‐Oviedo, & Peralta, ; Infante et al, ). The residual seeds from the juice industrialization and frozen pulp of yellow passion fruit ( Passiflora edulis ) are an important source of piceatannol, a natural stilbene that presents high antioxidant capacity (Matsui et al, ), anti‐inflammatory, vaso‐relaxing (Frombaum et al, ; Kinoshita et al, ; Sano, Sugiyama, Ito, Katano, & Ishihata, ; Seyed, Jantan, Bukhari, & Vijayaraghavan, ), antitumor, antidiabetic, and anti‐adipogenic properties (Kukreja, Mishra, & Tiwari, ; Piotrowska, Kucinska, & Murias, ; Uchida‐Maruki et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The residual seeds from the juice industrialization and frozen pulp of yellow passion fruit (Passiflora edulis) are an important source of piceatannol, a natural stilbene that presents high antioxidant capacity (Matsui et al, 2010), anti-inflammatory, vaso-relaxing (Frombaum et al, 2011;Kinoshita et al, 2013;Sano, Sugiyama, Ito, Katano, & Ishihata, 2011;Seyed, Jantan, Bukhari, & Vijayaraghavan, 2016), antitumor, antidiabetic, and anti-adipogenic properties (Kukreja, Mishra, & Tiwari, 2013;Piotrowska, Kucinska, & Murias, 2012;Uchida-Maruki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%